2015
DOI: 10.1073/pnas.1510574112
|View full text |Cite
|
Sign up to set email alerts
|

Motifs of VDAC2 required for mitochondrial Bak import and tBid-induced apoptosis

Abstract: Voltage-dependent anion channel (VDAC) proteins are major components of the outer mitochondrial membrane. VDAC has three isoforms with >70% sequence similarity and redundant roles in metabolite and ion transport. However, only Vdac2 −/− (V2 −/− ) mice are embryonic lethal, indicating a unique and fundamental function of VDAC2 (V2). Recently, a specific V2 requirement was demonstrated for mitochondrial Bak import and truncated Bid (tBid)-induced apoptosis. To determine the relevant domain(s) of V2 involved, VDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 51 publications
8
89
0
Order By: Relevance
“…Abramson and co-authors have found that zfVDAC2 forms 19 β-strands β-barrel with N-terminus located inside the pore very similar to mammalian or human VDAC1 with most difference found in alignments of the cytoplasmic loops connecting β-strands 1 and 2 or 5 and 6. In consistence with structural study (Schredelseker et al, 2014), Hajnoczky group[60] demonstrated that zfVDAC2 substitutes mammalian VDAC2 in inducing MOM permeabilization in Bak/tBid – induced apoptosis. Thus, both studies structural [53] and physiological[61] agree on that zfVDAC2 is a good model for mammalian VDAC2.…”
Section: Vdac Structure and Permeation Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abramson and co-authors have found that zfVDAC2 forms 19 β-strands β-barrel with N-terminus located inside the pore very similar to mammalian or human VDAC1 with most difference found in alignments of the cytoplasmic loops connecting β-strands 1 and 2 or 5 and 6. In consistence with structural study (Schredelseker et al, 2014), Hajnoczky group[60] demonstrated that zfVDAC2 substitutes mammalian VDAC2 in inducing MOM permeabilization in Bak/tBid – induced apoptosis. Thus, both studies structural [53] and physiological[61] agree on that zfVDAC2 is a good model for mammalian VDAC2.…”
Section: Vdac Structure and Permeation Propertiesmentioning
confidence: 99%
“…In a contrast, VDAC1 or 3 deficient mice are viable but characterized with impaired mitochondrial energetics [56, 59]. The major difference between mammalian VDAC2 and 1 is a small 11-amino acids extension of the N-terminus of VDAC2, but the latest study showed that this difference [53] is not account for a specific role of VDAC2 in import of Bak to mitochondria in apoptosis [60]. The only available so far structural data on VDAC2 have been obtained for zebra fish VDAC2 (zfVDAC2) which shares >90% of homology with mammalian VDAC2 and lacks the N-terminal extension.…”
Section: Vdac Structure and Permeation Propertiesmentioning
confidence: 99%
“…Furthermore, the alignment of the crystal structure of VDAC2 with the crystal structure of mVDAC1 (2.3 Å) [52] or hVDAC1 (4.1 Å) [51] offered an opportunity to evaluate the isoform-specific structural differences. We have used this approach recently to predict how the essential residues identified by systematic mutagenesis contribute to a potential protein–protein interaction of VDAC2 involved in the recruitment of Bak to the OMM [64]. Comparison of the superimposed structures of zfVDAC2 and mVDAC1 showed that N156 and E158 in VDAC1 form a closed area, whereas S156 and D158 in zfVDAC2 form the edge of an open “cup” (Fig.…”
Section: Structurementioning
confidence: 99%
“…4). Specifically VDAC2 has been linked to many cellular proteins, including Bak [17,64,65], stAR [35], Metaxin2 [66], Bcl-xS [67], RyR2 [68], eNOS (nitric oxide synthesize) [69], GSK3β [70], tubulin [71,72], Bax [73], BECN1-BCL2L1 [74] and Mcl1 [75]. Also, VP5, a viral protein from infectious bursal disease virus, has been demonstrated to interact with VDAC2 and Rack1 (receptor of activated protein kinase C1) in host cells [76,77].…”
Section: Interaction Partnersmentioning
confidence: 99%
“…Following the translocation of tBid into mitochondria, the outer membrane pore is opened and mitochondrial membrane potential (Δφ) collapses. At the terminus of the TRAIL signaling pathway, caspase-9 and its substrate caspase-3 are activated, which causes apoptotic cell death in cancers [32,33]. In this study, we found that the combination of miR-128 with TRAIL induced a significant upregulation of DR5 in CRC cells.…”
Section: Mir-128 Promotes Trail-induced Mitochondrial Apoptosis In Crcmentioning
confidence: 61%